Size separation of uncoated and polyethylene glycol coated silver nanoparticles using density gradient centrifugation - Mohamad Kasim, Amirah Shafilla (2021)
Purification of silver nanoparticles (AgNPs) is essential for biomedical field, where high purity and application are difficulty to have compatible size ranges of AgNPs as drug delivery. AgNPs in different size ranges, such as 1-20 nm, 20-40 nm, 40-60 nm, and 60-80 nm, would size uniformity AgNPs are required for drug delivery. Currently, the limitations in biomedical improve drug delivery efficacy. However, AgNPs with a wide range of sizes have disadvantage such as being toxic to health cells. Therefore, surface-bound chemical modification using coating agents such as polyethylene glycol (PEG) and purification procedures are required to generate smaller size ranges of AgNPs, which will also give a better understanding on the role of AgNPs’ physical properties in biomedical applications. In this study, uncoated AgNPs were produced via chemical and biological synthesis and then coated with PEG for its stability. UV-Visible spectrophotometer, high resolution-transmission electron microscope (HRTEM), Fourier-transform infrared spectroscopy (FTIR), and dynamic light scattering (DLS) were used to characterise uncoated and PEG-coated AgNPs from chemical and biological synthesis for size, shape and morphology. The size distribution of PEG-coated AgNPs from both synthesis methods are slightly bigger around 1 – 3 nm compared to the uncoated AgNPs from both synthesis methods. Further, the shape of PEG-coated AgNPs from both synthesis methods revealed predominant spherical shape (86.86%). It showed that PEGcoated AgNPs from both synthesis methods was homogenous in term of size, shape and morphology compared to the uncoated AgNPs from both synthesis methods. In addition, a purification method which is density-gradient centrifugation (DGC) was carried out on the both uncoated and PEG-coated AgNPs from both synthesis methods by using sucrose at concentration ranging from 10% to 50% (w/v). Based on the results from UV-Visible spectrophotometer and HR-TEM, the size ranges of uncoated and PEG-coated AgNPs from both synthesis methods after purification was smaller than the crude one. In comparison to uncoated AgNPs from both synthesis methods, PEG-coated AgNPs from both synthesis methods obtained desired separated size ranges. Hence, the PEG- coated AgNPs from both synthesis methods are ideal for drug delivery in biomedical applications.